COMPARATIVE ANALYSIS OF PHYSICAL AND MECHANICAL PROPERTIES OF WOOD FROM THREE PLANTATION SOFTWOODS - Santini, Elio José (2000)
Woods from plantation stands of parana, slash and loblolly pines, thinned at least once, were tested with the objective of comparing physical and mechanical properties. Five threes from each specie were harvested from selected stands. The stems were bucked into logs and then transported to the sawmill cooperating in this study. The logs were processed into planks, which were air seasoned, and then cut into pieces according to ASTM standards. Although the average strength of parana pine was slightly larger than the two other pines, significant differences were found only in the tests of static bending (modulus of elasticity and tension at the proportional limit), compression parallel to the grain (maximum crushing strength, modulus of elasticity and tension at the proportional limit) and hardness (cross-section). The  properties  were  not  different  for  slash  and loblolly pines, except in tension perpendicular to the grain, where the strength of loblolly pine was higher than the others. No differences were found for specific gravity and shrinkage among the species.